Answering Savings Puzzle About Small Saving Schemes and Mutual Funds: Evidence from Tripura. Issue 1 (June 2019) - Deb, Rajat; Deb, Prasenjit; Majumder, Sujit; Chakraborty, Sourav; Chakraborty, Kiran Sankar
The study has motivated to assay the comparatively better saving tool—small saving schemes or mutual funds—based on empirical evidence. The related literature has been extensively reviewed to frame a conceptual model and has adopted survey strategy with stratified random sampling technique for gathering data from 150 respondents. Inferential statistics have supported to reject the null hypotheses and has concluded that selective demographics, risk, returns, tax benefits, inflation beating capability, and liquidity significantly influence in savings. The national saving certificate and fixed deposits have been identified as most preferred saving instruments while mutual funds have also been gaining popularity. Policy implications have been derived from the study.